Sono-hydro priming process (ultrasound modulated hydration): Modelling hydration kinetic during paddy germination - Kalita, Dipsikha (Ultrason Sonochem, 2020)
Application of ultrasound technology in modulating the hydration process during paddy germination was analyzed in this study. The effect of hydropriming (24 h) and sono-hydro priming (ultrasound priming, 12 h) on the hydration behaviour of paddies was determined at different temperatures (25–40 °C). Ultrasound pulse was applied for 10 min after every one hour for sono-hydro priming. Germination potential and microstructure analysis of treated paddies were also performed. Downward concave curve observed in hydration process of paddies indicates initial high-water absorption through diffusion process. Sono-hydro priming process showed higher hydration rate compared to hydropriming. The changes in moisture content during hydration processes fitted to theoretical (Fick's model) and empirical model (Peleg model) exhibited high regression coefficient (R(2) > 0.95) indicating suitability for predicting hydration behaviour in both paddies for germination. The Peleg model adequately predicted saturation moisture content and sono-hydro priming efficiently increased the water absorption rate. Effective moisture diffusivity determined from Fick's diffusion model increased for sono-hydro priming. Activation energy estimated from effective moisture diffusivity required in sono-hydro priming (E(a) = 20.32 and 19.19 KJ/mol respectively) for pigmented rice and non-pigmented rice was lower than hydropriming (E(a) = 27.11 and 32.15 KJ/mol respectively). Both hydration processes were endothermic and non-spontaneous inferred from thermodynamic properties. Sono-hydro priming exhibited < 95% germination potential with shorter soaking time (12 h) owing to the high mass transfer rate. SEM micrograph revealed water absorption through various micro-cavities during sono-hydro priming. Thus, sono-hydro priming potentially reduced the soaking process (approximately 50%) with higher germination rate in paddies beneficial for commercial malting of grains.